Determining the critical speed for hunting of three-piece freight bogies: practice versus simulation approaches. Issue 10 (3rd October 2022) - Skerman, Don; Cole, Colin; Spiryagin, Maksym
Abstract : Hunting causes accelerated wear and damage to bogies, track and the lading carried by railway wagons and can, in conjunction with track geometry irregularities, lead to derailment. Simulation can be used to estimate the critical speed below which sustained hunting will not occur given certain parameters of the wagon, track and lading. This paper investigates the hunting of an unloaded freight wagon fitted with three-piece bogies which utilise friction wedges for damping and have friction at many interfaces. Several methods of analysis are compared including simulation on track with irregularities. The novel use of different initial conditions at each bogie is shown to excite different types of hunting at a given speed. Only one of these was excited by the common method of running over a discrete lateral track irregularity.